Metal-Matrix Hardmetal/Cermet Reinforced Composite Powders for Thermal Spray - Dmitri GOLJANDIN; Heikki SARJAS; Priit KULU; Helmo KÄERDI; Valdek MIKLI (Medžiagotyra, 2012)
Recycling of materials is becoming increasingly important as industry response to public demands, that resources must be preserved and environment protected. To produce materials competitive in cost with primary product, secondary producers have to pursue new technologies and other innovations. For these purposes different recycling technologies for composite materials (oxidation, milling, remelting etc) are widely used. The current paper studies hardmetal/cermet powders produced by mechanical milling technology. The following composite materials were studied: Cr3C2-Ni cermets and WC-Co hardmetal. Different disintegrator milling systems for production of powders with determined size and shape were used. Chemical composition of produced powders was analysed.  To estimate the properties of recycled hardmetal/cermet powders, sieving analysis, laser granulometry and angularity study were conducted. To describe the angularity of milled powders, spike parameter–quadric fit (SPQ) was used and experiments for determination of SPQ sensitivity and precision to characterize particles angularity were performed. Images used for calculating SPQ were taken by SEM processed with Omnimet Image Analyser 22. The graphs of grindability and angularity were composed. Composite powders based on Fe- and Ni-self-fluxing alloys for thermal spray (plasma and HVOF) were produced. Technological properties of powders and properties of thermal sprayed coatings from studied powders were investigated. The properties of spray powders reinforced with recycled hardmetal and cermet particles as alternatives for cost-sensitive applications were demonstrated. DOI: http://dx.doi.org/10.5755/j01.ms.18.1.1348